Biosonar resolving power: echo-acoustic perception of surface structures in the submillimeter range - Simon, Ralph; Knörnschild, Mirjam; Tschapka, Marco; Schneider, Annkathrin; Passauer, Nadine; von Helversen, Otto (Frontiers in Physiology, 2014)
The minimum distance for which two points still can be separated from each other defines the resolving power of a visual system. In an echo-acoustic context, the resolving power is usually measured as the smallest perceivable distance of two reflecting surfaces on the range axis and is found to be around half a millimetre for bats employing frequency modulated echolocation calls. Only few studies measured such thresholds with physical objects, most often bats were trained on virtual echoes i.e. echoes generated and played back by a computer; moreover, bats were sitting while they received the stimuli. In these studies differences in structure depth between 200 µm and 340 µm were found. However, these low thresholds were never verified for free-flying bats and real physical objects. Here, we show behavioural evidence that the echo-acoustic resolving power for surface structures in fact can be as low as measured for computer generated echoes and even lower, sometimes below 100 µm. We found this exceptional fine discrimination ability only when one of the targets showed spectral interferences in the frequency range of the bats' echolocation call while the other target did not. This result indicates that surface structure is likely to be perceived as a spectral quality rather than being perceived strictly in the time domain. Further, it points out that sonar resolving power directly depends on the highest frequency/shortest wavelength of the signal employed.